(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
Chitosan has been used as an adsorbent to remove remazol red RR from aqueous solution by adsorption. The experiments have been conducted to study the effects of initial concentration of adsorbate, temperature, pH and particle size on dye adsorption. The kinetic data obtained have been examined using pseudo first- and pseudo second-order equations. The equilibrium adsorption data have been studied by using Freundlich and Langmuir models. The best results have been achieved with the pseudo second-order kinetic model and with the Langmuir equilibrium isotherm model. The equilibrium adsorption capacity (qe) of chitosan increases with increasing the initial concentration of dye, temperature and with decreasing particle size. However, the highest adsorption capacity has been found at a pH about 5.4. The maximum monolayer adsorption capacity, qe = 155.72 mg/g has been found at the optimum conditions. The activation energy (Ea) of sorption kinetics is about 9.25 kJ/mol. Thermodynamic parameters such as change in free energy (?G), enthalpy (?H) and entropy (?S) have also been evaluated. DOI: http://dx.doi.org/10.3329/bjsir.v49i2.22005 Bangladesh J. Sci. Ind. Res. 49(2), 111-118, 2014